Design and Implementation of Network Security Systems on Virtualized Networks - Akmal Baharuddin Syam; Rakhmadi Rahman (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2024)
This report, entitled